Analisis Keamanan Aplikasi RememberMe! Menggunakan Metode Vulnerability Assessment - Arlyn Chanarly, Rayner; Abdul Munir S; Hendra Surasa (STMIK KHARISMA Makassar, 2024)
RememberMe! application is a mobile password manager application designed to solve problems regarding passwords where users must remember the passwords used for each site and application. This research aims to measure the security level of RememberMe! application to find out whether RememberMe! application is safe to use for users. The results of this research are then expected to be a reference for developers in making improvements and further development so that the RememberMe! application is more secure and useful for users. By using the Vulnerability Assessment method, testers can scan the RememberMe! application against all possible test cases and look for existing gaps and weak points of the RememberMe! application. This process involves a Static Analysis of the application for potential vulnerabilities, including poor or improper application configuration, software flaws, and other operational weaknesses in processes or technical countermeasures. Vulnerability Assessment can test overall, integrated, operational, and reliable.